Cytokine‐Producing B Cells Promote Immune‐Mediated Bile Duct Injury in Murine Biliary Atresia. Issue 5 (10th July 2018) - Bednarek, Joseph; Traxinger, Brianna; Brigham, Dania; Roach, Jonathan; Orlicky, David; Wang, Dong; Pelanda, Roberta; Mack, Cara L.
Abstract : Biliary atresia (BA) is a neonatal T cell–mediated, inflammatory, sclerosing cholangiopathy. In the rhesus rotavirus (RRV)–induced neonatal mouse model of BA (murine BA), mice lacking B cells do not develop BA, and the lack of B cells is associated with loss of T‐cell and macrophage activation. The aim of this study was to determine the mechanism of B cell–mediated immune activation (antigen presentation versus cytokine production) in murine BA. Normal neonatal B cells in the liver are predominantly at pro‐B and pre‐B cellular development. However, BA mice exhibit a significant increase in the number and activation status of mature liver B cells. Adoptively transferred B cells into RRV‐infected, B cell–deficient mice were able to reinstate T‐cell and macrophage infiltration and biliary injury. Nonetheless, neonatal liver B cells were incompetent at antigen presentation to T cells. Moreover, 3‐83 immunoglobulin transgenic mice, in which B cells only present an irrelevant antigen, developed BA, indicating a B‐cell antigen–independent mechanism. B cells from BA mice produced a variety of innate and adaptive immune cytokines associated with immune activation. In vitro trans‐well studies revealed that BA B cells secreted cytokines that activated T cells based on increased expression of T‐cell activation marker cluster of differentiation 69. Conclusion : Neonatal liver B cells are highly activated in murine BA and contribute to immune activation through production of numerous cytokines involved in innate and adaptive immunity; this work provides increased knowledge on the capacity of neonatal B cells to contribute to an inflammatory disease through cytokine‐mediated mechanisms, and future studies should focus on targeting B cells as a therapeutic intervention in human BA.